BUDAYA ORGANISASI ISLAMI SEBAGAI FONDASI MANAJEMEN LEMBAGA PENDIDIKAN BERKUALITAS - Anton Sulaiman; Ulfain Ulfain; Fahmi Abdullah (Universitas Islam Bunga Bangsa Cirebon, 2022)
Islamic organizational culture represents a foundational yet underexplored determinant of management quality in Islamic educational institutions. While organizational culture has received extensive attention in management literature broadly, its specific manifestation within Islamic educational contexts, and its operational relationship to management quality, remains insufficiently theorized. This study aims to analyze Islamic organizational culture as a foundational element of quality management in Islamic educational institutions, examining its conceptual dimensions, manifestations, and functional contributions. A systematic library research approach was employed, utilizing peer-reviewed articles, scholarly books, and policy documents published between 2019 and 2024. Findings demonstrate that Islamic organizational culture, when operationalized through values of tawhid, amanah, shura, and 'adalah, creates enabling conditions for quality management by fostering collective commitment, ethical accountability, and purposive collaboration. The study identifies a critical research gap: existing literature treats Islamic values and management quality as parallel concerns rather than as causally integrated phenomena. This paper proposes a Values-Driven Management Quality (VDMQ) framework that positions Islamic organizational culture as the transformative foundation of institutional excellence.